Consumer value and value co-creation in complementary and alternative medicine (CAM) health services : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Marketing at Massey University, Albany, New Zealand - Dodds, Sarah Louise (Massey University, 2015)
This thesis contributes to an emergent area on consumer value co-creation in a rapidly growing and exciting ‘new’ service market, Complementary and Alternative Medicine (CAM) health services. The market for CAM health services is experiencing strong growth as consumers look for greater value, choice and control in managing their health. Despite the growth in this large health service market there is a paucity of research from a service marketing and consumer behaviour perspective. Yet, understanding what CAM consumers’ value and how they co-create value with CAM health services has important managerial implications. The purpose of this research is to explore what value CAM consumers’ gain and how they co-create value from their consumption experiences with CAM health services. The research adopts an interpretive approach employing an exploratory case study research strategy, using qualitative methods and an adapted version of the visual elicitation technique ZMET. The research process is semi-longitudinal and is conducted in three phases over a 12 month period. Sixteen CAM consumers with ‘lifestyle’ health complaints who use CAM health services participated in the study. The findings reveal eight consumer value components including: quality of care, treatment efficiency, physical environment, esteem value, social value, spiritual value, ethics and play. A consumer value model for CAM health services and potentially all health care services is proposed. Significantly this research found that CAM consumers co-create value on three levels according to their: approach to health care, preferred ‘consumer value co-creation relationship styles’ and engagement in ‘consumer value co-creation activities’. Consequently this thesis presents a typology of consumer value co-creation in CAM health services and develops a consumer value co-creation framework that can potentially be used for all health services. This research contributes to service marketing and consumer behaviour theory by extending the concepts of ‘consumer value’ and ‘value co-creation’ to incorporate findings from the CAM health service sector. The managerial implications of this research could help guide both CAM health care and mainstream medical practices to provide better health services and ultimately improved health outcomes for health care consumers. Future research could implement the unique three phase semi-longitudinal process and visual methods developed in this research, in various health care and service settings.
Listed in 2016 Dean's List of Exceptional Theses
Keywords: Alternative medicine; Marketing; Complementary medicine; Dean's List of Exceptional Theses